Technology Development Multidimensional Review for Engineering and Technology Managers - Daim, Tugrul U; Neshati, Ramin; Watt, Russell; Eastham, James (Innovation, Technology, and Knowledge Management, 2014)
Developing new products, services, systems, and processes has become an imperative for any firm expecting to thrive in todayâ_Ts fast-paced and hyper-competitive environment.Â  This volume integrates academic and practical insights to present fresh perspectives on new product development and innovation, showcasing lessons learned on the technological frontier.Â  The first part emphasizes decision making.Â  The second part focuses on technology evaluation, including cost-benefit analysis, material selection, and scenarios. The third part features in-depth case studies to present innovation management tools, such as customer needs identification, technology standardization, and risk management. The fourth part highlights important international trends, such as globalization and outsourcing. Finally the fifth part explores social and political aspects.